2016
DOI: 10.1167/iovs.16-19126
|View full text |Cite
|
Sign up to set email alerts
|

The Initiation of Smooth Pursuit is Delayed in Anisometropic Amblyopia

Abstract: PurposeSeveral behavioral studies have shown that the reaction times of visually guided movements are slower in people with amblyopia, particularly during amblyopic eye viewing. Here, we tested the hypothesis that the initiation of smooth pursuit eye movements, which are responsible for accurately keeping moving objects on the fovea, is delayed in people with anisometropic amblyopia.MethodsEleven participants with anisometropic amblyopia and 14 visually normal observers were asked to track a step-ramp target m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…While amblyopic eyes show poorer fixation stability than control eyes during both monocular and binocular viewing, fellow eyes have fixation stability comparable to that of controls, both when fixating or under binocular viewing . However, the initiation of tracking pursuits is delayed and saccadic latency of the non‐amblyopic eye can be less accurate than in age‐matched controls …”
Section: Visual Deficits In Amblyopiamentioning
confidence: 94%
See 1 more Smart Citation
“…While amblyopic eyes show poorer fixation stability than control eyes during both monocular and binocular viewing, fellow eyes have fixation stability comparable to that of controls, both when fixating or under binocular viewing . However, the initiation of tracking pursuits is delayed and saccadic latency of the non‐amblyopic eye can be less accurate than in age‐matched controls …”
Section: Visual Deficits In Amblyopiamentioning
confidence: 94%
“…Oculomotor deficits including inaccurate or unsteady fixation, delayed and more variable initiation of saccades, and inaccurate tracking pursuits have been recorded in amblyopic subjects . While amblyopic eyes show poorer fixation stability than control eyes during both monocular and binocular viewing, fellow eyes have fixation stability comparable to that of controls, both when fixating or under binocular viewing .…”
Section: Visual Deficits In Amblyopiamentioning
confidence: 99%
“…In contrast, individuals with anisometropic amblyopia show relativity fewer deficits. Specifically, a recent study showed that the mean pursuit gain of both eyes was comparable to visually normal controls; however, pursuit initiation was slightly delayed (~20 ms), and the gain was more variable in the amblyopic eye [107].…”
Section: Effects Of Amblyopia On the Oculomotor Systemmentioning
confidence: 99%
“…Moreover, recovery from amblyopia is expedited by tasks requiring coordination of hand and eye movements, such as having patients manipulate objects during visual training as reviewed in Daw, in 2013. Several researchers have pointed out that patients with amblyopia exhibit oculomotor impairments including problems with saccadic eye movements,[80] smooth pursuit,[81] fixation stability,[82] hand--eye coordination,[83] thus suggesting that targeting visuomotor circuits during treatment may help to alleviate some of these deficits. [84]…”
Section: What Are the Treatment Options?mentioning
confidence: 99%